Perbedaan hasil penghitungan tempat yang dibutuhkan dengan metode prediksi Sitepu, Nourallah dan pengukuran langsung (Difference of required space measurement with Sitepu, Nourallah prediction method and direct measurement) - Andreas Joko Wiyono (Faculty of Dental Medicine, Universitas Airlangga, 2016)
Backgrounds: The determination of a tooth-size to arch-length discrepancy in the mixed dentition requires an accurate prediction of the mesiodistal widths of the unerupted permanent teeth. This is an essential factor in orthodontic treatment planning.Purpose: The aim of this study was to compare and validate Sitepu analysis with Nourallah analysis on study models of Deutero Malays patients. Methods:This observational descriptive study was conducted on 50 models of study patients treated in Orthodontic Clinic at School of Dental Medicine of Airlangga University. The witdth of maxillary and mandibulary canines, first and second premolars were measured with prediction formula of Sitepu, prediction formula of Nourallah and direct measurement. The measurement results were analyzed statistically with One-way ANOVA followed by LSD test. Result:The results showed that in the lower jaw there was no significant difference between the Nourallah prediction methods, Sitepu prediction methods, as well as direct measurements (p > 0.05); but maxillary measurement found a significant difference (p = < 0.05). LSD test indicated that the maxillary measurements in the upper jaw found a significant difference between the direct measurement with Nourallah prediction methods and the Sitepu prediction method with Nourallah prediction method. Conclusion:Sitepu analysis is more accurate in predicting unerupted mandibular and maxillary canines and premolars on Deutero Malays patients. Nourallah analysis is more accurate then Sitepu analysis in predicting unerupted mandibular canines and premolars.